Fotgängares singelolyckor : En studie av halkolyckor i Luleå - Östman, Andreas (2014)
In an accessible and attractive winter city inhabitants should be able to move anywhere by foot without feeling insecure due to slipping. The climate along the northern coast of Sweden is expected to become warmer over time, resulting in warmer winters and therefore more days with a high risk of slipping. This thesis explores the phenomenon of slipping in Luleå and tries to answer questions such as where pedestrians slips, how the society could prevent slipping accidents and the pros and cons with the anti-skid methods used today to prevent pedestrians from slipping.To answer these questions, various methods such as interviews, literature reviews, data collection of accident data and measurement of the slope was used to get a wide approach and a bigger understanding of the problem.The thesis showed that neither production managers of Luleå municipality nor the interviewed real estate managers consider that slipping accidents burden them as they hardly get any slipping accidents reported. But the analysis of accident data from the accident database STRADA show that approximately 1200 slipping accidents have occurred in Luleå during the ten years (2003- 2013) studied. The result from this study in Luleå acknowledges earlier research findings in the field and thus showed that more old people than young people slip. More women than men slips and most accidents involve older women. It is also women who have been accountable for most of the health care as a result of the serious injuries they have sustained.The probability that a slipping accident occurs is higher in neighborhoods where there are more pensioners living and where the daytime population is high. The majority of the slipping accidents have occurred along the main street in the city center. Outside the center area the accidents usually occurred around the neighborhood centers and the parking areas next to them. It is in these places most people are moving by foot. But many accidents have also occurred on streets in general and on residential streets where ...